Analysis the Effect of Financial Performance on Corporate Social Responsibility - Panchal, Sarita; Rao, Pyla Narayana (International Journal of Sustainability in Research, 2024)
CSR stands for corporate social responsibility. growing field of Knowledge and needs more focus and citations from researchers to develop. The objective of this study is to examine the relationship between corporate social responsibility and financial performance of companies in the Indian context. The accounting - based indicator EPS is employed to quantify the financial company performance. We Pull fixed-effects and pooled regression models to examine the Impact of CSR on the financial performance of the Bombay Stock Exchange SENSEX 30 companies in India. The empirical research uses panel data. of the Bombay Stock exchange SENSEX 30 companies for the period 2016 and 2023. The main results indicate that CSR does not have a significant impact on EPS. We have also done sector investigation to look into the relationship between financial performance and CSR. We have selected 2 sectors that have the highest number of companies listed in BSE SENSEX 30 (The Software sector has 5 companies and the banking sector has 6 companies). We found that CSR does not have a favorable effect on EPS for software and banking industry companies.